2020
DOI: 10.1126/sciadv.aay8491
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering atomistic mechanisms of the gas-solid interfacial reaction during alloy oxidation

Abstract: Gas-solid interfacial reaction is critical to many technological applications from heterogeneous catalysis to stress corrosion cracking. A prominent question that remains unclear is how gas and solid interact beyond chemisorption to form a stable interphase for bridging subsequent gas-solid reactions. Here, we report real-time atomic-scale observations of Ni-Al alloy oxidation reaction from initial surface adsorption to interfacial reaction into the bulk. We found distinct atomistic mechanisms for oxide growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…This study, however, reveals dissociative adsorption of hydroxyl groups during in situ heating, which causes continuous anisotropic NiO growth. Luo and coworkers propose that mechanical stress at the Ni/NiO interface affects oxidation rates in water, 24 which supports the observation of NiO growth only on select surfaces of the utilized Ni nanoparticles.…”
Section: 𝑎𝑑mentioning
confidence: 62%
See 3 more Smart Citations
“…This study, however, reveals dissociative adsorption of hydroxyl groups during in situ heating, which causes continuous anisotropic NiO growth. Luo and coworkers propose that mechanical stress at the Ni/NiO interface affects oxidation rates in water, 24 which supports the observation of NiO growth only on select surfaces of the utilized Ni nanoparticles.…”
Section: 𝑎𝑑mentioning
confidence: 62%
“…Proposed growth mechanisms rely on cation diffusion along the screw dislocation cores, that is, the longitudinal direction of the whiskers, while lattice diffusion is responsible for lateral growth. This mechanism was initially proposed by Tallman and Gulbransen 22 for the formation of 𝛼-Fe 2 O 3 whiskers during the oxidation of iron at 400-500 • C. Several studies on Ni alloys have demonstrated different oxidation behaviors in water vapor environments compared to molecular oxygen gas [23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Significant advances in both experimental and computational methods have enabled advances in how we visualize and describe material microstructures. For example, three dimensional microstructures can be visualized with techniques such as serial sectioning and atom probe tomography [1,2], and in situ methods have been developed for direct visualization of atomic-scale phenomena, including oxide growth mechanisms and element redistribution [3,4]. Computational methods have been at the forefront of many materials research studies due to the need for accelerated materials discovery, design, and development emphasized in the Materials Genome Initiative [5].…”
Section: Introductionmentioning
confidence: 99%